How Understandardisation in Assessment Methods Influences Student Performance and Motivation - Oyeronke Christiana Paramole (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
Assessment methods in education significantly influence student performance and motivation. However, standardisation—characterised by variability and inconsistency in assessment practices—challenges educators and learners alike. This research explores the impact of standardisation on student outcomes through a systematic literature review (SLR). The SLR synthesised existing studies to identify key themes regarding the correlation between assessment methods and student performance, the role of feedback, and the importance of fairness in assessments. Significant findings indicate that formative assessments enhance academic performance by providing ongoing feedback, while perceived fairness in assessments boosts student motivation and engagement. Additionally, varied assessment methods contribute to developing lifelong learning skills essential for success beyond the classroom. The study concludes that while traditional standardisation offers consistency, standardisation presents unique benefits that can foster a more equitable and effective educational environment. This research contributes to the field by highlighting the need for flexible assessment practices that cater to diverse student needs, offering recommendations for educators and policymakers to enhance assessment strategies and promote improved educational outcomes. Ultimately, this work underscores the importance of ongoing exploration in educational assessment to create inclusive learning environments that support all students.